Grand theft in international law. Issue 3 (9th November 2022) - Kulamadayil, Lys
Abstract: Commonly subsumed under the legal concepts of corruption and money-laundering, the theft of public wealth on a massive scale with the aid of transnational financial institutions has, so far, largely been neglected by legal scholarship and legal practise. Drawing on two grand theft cases, this article's objectives are threefold. Firstly, it explains the concept of grand theft by illustrating how it operates. Secondly, it retraces legal responses to grand theft in jurisdictions of countries, which are home to key financial markets places, to highlight the strengths and weaknesses of this legal regime in practice. Thirdly, it reflects on the obstacles to researching grand theft.